Politically Motivated Selective Exposure and Perceived Media Bias. (February 2020) - Barnidge, Matthew; Gunther, Albert C.; Kim, Jinha; Hong, Yangsun; Perryman, Mallory; Tay, Swee Kiat; Knisely, Sandra
If the individuals who are most likely to perceive media bias no longer encounter, via selective exposure, media content they might consider biased, why are perceptions of media bias so pervasive? We argue that many people who engage in politically motivated selective exposure also perceive "the media" in general to be biased. Relying on a survey of adults in the U.S. state of Wisconsin, which has witnessed particularly contentious and divisive political events since 2011, this study examines self-reported patterns of selective exposure to partisan media while accounting for the role of the local communication ecology in encouraging or discouraging partisan media selectivity. It also tests the idea that selective exposure is related to a generalized perception of media bias—the idea that "the media" in general are biased while self-selected media are not. Finally, the study tests a moderated mediation model showing the structure of relationships among political opinion extremity, selective exposure, and perceived media bias. Results suggest (a) a positive relationship between political opinion extremity and selective exposure, (b) opposite patterns of relationships between selective exposure and perceived media bias about self-selected and general media, respectively, and (c) evidence of moderated mediation among political opinion extremity, selective exposure, and perceived media bias.